Review of Modifications of Learning Physical Education for Sports and Health (PPJOK) in Public Elementary School 07 Pulau Air - Lasri, Riska Ramadani; Rahmi, Miftah Fajrin; Sulasri, Sulasri (Yayasan Sekora, 2018)
This research originated from the fact that in schools there are still many students who are less motivated in participating in the Physical Education and Health (PJOK) learning, due to the lack of ability of PJOK teachers in implementing learning, especially in implementing modification. The purpose of this study was to determine 1) Application of modification of equipment in implementing PJOK learning at SD Negeri 07 Pulau Air, 2) Application of field modification in implementing PJOK learning at SD Negeri 07 Pulau Air, 3) Application of modification of game rules in implementing PJOK learning in SD Negeri 07 Water Island. This research was conducted using descriptive research methods. This research was conducted at SD Negeri 07 Pulau Air, Padang City in April 2011. The population of this study were all students of SD Negeri 07 Pulau Air from grades I - VI, totaling 241 people. The sampling technique used purposive sampling. Based on the research results, it was found that the equipment modification was 57.07% in the sufficient category, the field modification of 50.98% was included in the sufficient category and the modification of the game rules by 61.69% was included in the good category. From these results it can be concluded that the modification of the equipment, field and game regulations at SD Negeri 07 Pulau Air, Padang City is sufficient, but still needs to be improved. For this reason, it is hoped that the physical education teacher at SD Negeri 07 Pulau Air, Padang City can improve their ability in implementing physical education learning, especially in the ability to make modifications.